Whiteness index prediction of para rubber sheet during hot air drying - Rattanamechaiskul, Chaiwat; Junka, Nittaya; Potichalung, Jakkrit; Wingwon, Thawatchai; Boontum, Wattana; Srisang, Naruebodee (Engineering and Applied Science Research, 2016)
This research’s objective was to study the color change by analyzing whiteness index (WI) of unsmoked sheet (USS) during hot air drying at different temperatures compared with reference USS dried by sun drying. Result data then was used to develop the equation to predict the WI change by response surface methodology (RSM). The times to dry the raw para rubber sheet (RPRS) at initial moisture content of 25.0±2.0 % dry basis (d.b.) with hot air temperature of 50, 60 and 70˚C to final moisture content of 3.0±1.0 % d.b. were 68, 44 and 16 hr, respectively. At the final moisture content, WI values of the dried USS were 48.8, 50.1 and 54.5, respectively, whereas that value of reference USS was 43.3. Consequently, the brown color of dried USS by hot air was not darker than the reference USS and regarded good quality color. In addition between the first and second degree models of WI prediction, it was found the second degree model was better with a mean of coefficient of determination (R2) of 0.9424.